Insights into Acute Coronary Syndrome: A Study of Patient Characteristics in Dr. Rivai Abdullah Public Hospital - Zerlinda, Zabrina; Azmar, Erwin; Rosdah, Ayeshah Augusta (eJournal Kedokteran Indonesia, 2025)
Acute Coronary Syndrome (ACS) remains a leading cause of morbidity and mortality worldwide, with variations in patient characteristics and risk factors across regions. In Indonesia, especially in resource-limited settings, data on the demographic and clinical features of ACS are limited. Such information is crucial for guiding management strategies. This study analyzed secondary data from medical records of 86 ACS patients admitted to Dr. Rivai Abdullah Public Hospital between January and December 2023. This cross-sectional study included new and existing patients with acute coronary syndrome who had complete demographic, clinical, and electrocardiographic data. In contrast, patients with incomplete data or congenital heart disease were excluded. The research was conducted between July and September 2024. Of these patients, 64% were male, and 51.16% were aged 41 to 60 years. Nearly half (46.51%) had only primary education, and 25.58% were farmers or housewives. Hypertension was the most common comorbidity (66.28%), followed by diabetes mellitus (25.58%), obesity (18.60%), and dyslipidemia (5.81%). Electrocardiographic findings showed that 55.81% had ST-elevation myocardial infarction (STEMI), mainly involving the anteroseptal region. Meanwhile, 44.19% had non-ST-elevation myocardial infarction (NSTEMI), with T-wave inversion present in 42.11% of these cases. These results indicate that ACS mainly affects middle-aged males with low education and informal occupations. Hypertension was the leading risk factor, and STEMI was the most common presentation. Targeted prevention and early detection are vital to improving outcomes in this population.